Molecular analysis of the Pygospio elegans group of species (Annelida: Spionidae) - Radashevsky, Vasily I.; Pankova, Victoria V.; Neretina, Tatyana V.; Stupnikova, Alexandra N.; Tzetlin, Alexander B. (Zootaxa, 2016)
Pygospio elegans Claparède, 1863, the type species of the genus Pygospio, was originally described from Normandy, France, and later widely reported from boreal waters in the northern hemisphere. Sequence data of four gene fragments (2576 bp in total) of the mitochondrial 16S rDNA, nuclear 18S and 28S rDNA, and Histone 3 have shown that individuals from California and Oregon, USA, Scotland and the White Sea, Russia were genetically similar (the average p-distances for the combined data between the four groups ranged from 0.04 to 0.16%, average p = 0.1%). These individuals are considered to be conspecific and the amphiboreal distribution of P. elegans is here confirmed. Adult morphology of the species is briefly described and illustrated. The molecular analysis revealed two genetically distant populations, Pygospio sp. 1 from the Sea of Okhotsk and Pygospio sp. 2 from Oregon. The morphological differences and high average genetic p-distances for the combined data (ranging from 3.06 to 3.18%, average p = 3.12%) between Pygospio sp. 2 and P. elegans suggest the presence of an undescribed Pygospio species co-occurring with P. elegans in Oregon. High morphological similarity and moderate genetic p-distances for the combined data (ranging from 1 to 1.11%, average p = 1.07%) between Pygospio sp. 1 and P. elegans indicate a comparatively recent genetic divergence of the Pygospio population in the Sea of Okhotsk. Taking into account the high genetic similarity of the remote European and North American populations of P. elegans and medial location of the Pygospio sp. 1 population, we suggest the latter to belong to a separate species. However, this conclusion should be verified in further studies on the morphology, reproductive biology and genetics of this population. The present findings show the need to re-examine Pygospio from the Asian Pacific and elsewhere that have been identified as P. elegans.